2012
DOI: 10.1186/1746-4811-8-46
|View full text |Cite
|
Sign up to set email alerts
|

Plant lighting system with five wavelength-band light-emitting diodes providing photon flux density and mixing ratio control

Abstract: BackgroundPlant growth and development depend on the availability of light. Lighting systems therefore play crucial roles in plant studies. Recent advancements of light-emitting diode (LED) technologies provide abundant opportunities to study various plant light responses. The LED merits include solidity, longevity, small element volume, radiant flux controllability, and monochromaticity. To apply these merits in plant light response studies, a lighting system must provide precisely controlled light spectra th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 58 publications
(63 reference statements)
2
29
0
Order By: Relevance
“…A reduction in quantum efficiency (PSII) in the B LED-treated leaves may activate energy distribution in the photosystem, increase non-photochemical quenching (NPQ), and protect the leaf from LED-light injury [16,50]. In contrast, a lower rate of photosynthesis was found in R LED-treated leaves in lettuce [51], rice [52], and wheat [53]. Consequently, the lower rate of photosynthesis occurred due to low N-content of leaves under R LEDs with lower chlorophyll content [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A reduction in quantum efficiency (PSII) in the B LED-treated leaves may activate energy distribution in the photosystem, increase non-photochemical quenching (NPQ), and protect the leaf from LED-light injury [16,50]. In contrast, a lower rate of photosynthesis was found in R LED-treated leaves in lettuce [51], rice [52], and wheat [53]. Consequently, the lower rate of photosynthesis occurred due to low N-content of leaves under R LEDs with lower chlorophyll content [17].…”
Section: Discussionmentioning
confidence: 99%
“…Stomatal conductance (g s ), a photosynthesis parameter, is a bridge for gas exchange and water transpiration, and is significantly correlated with the light spectrum ( Figure 3) [53,55,56]. CO 2 diffuses through the leaf stomata to be used for photosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the previous studies concluded that a controlled and tailored light spectral composition can be useful for inducing specific plant responses, and also for enhancing nutritional value in vegetables [19][20][21]. In [25] authors studied the effect of red plus three short-wavelength lights (near-UV, blue, and cyan) on lettuce and concluded that the optimal growth was obtained with red and blue treatment which caused a higher carbohydrate content; in fact about the 90% of light absorption by plant leaves is in the blue and red bands [26].…”
Section: Introductionmentioning
confidence: 99%
“…In [17], blue light influenced leaf morphogenesis, promoting differentiation of mesophyll cells and the formation of intercellular spaces, also having positive effects on leaf thickness and area. Light in the blue wavelengths promotes chloroplast development and increases net photosynthesis, the number of stomata and the thickness of leaves in cherry tomato plants [18]; blue light also induces a phototropic curvature of oat coleoptiles in the direction of light [19]. Even if the net CO 2 assimilation rate is reduced, rose growth under blue light alone presents a three-day slower, but more complete, vegetative and floral development [20].…”
Section: Introductionmentioning
confidence: 99%
“…The pura e-mail: htkim@kitech.re.kr b e-mail: stkim@kitech.re.kr c e-mail: jongseok@kitech.re.kr d e-mail: kcjin@kitech.re.kr e e-mail: hskim@kitech.re.kr Figure 1. Concept of color selection and light mixing pose can involve improving the image quality, [10] determining optical spectrum, [11] and aiming desired color coordinate. [12] Commercial LEDs have typical colors.…”
Section: Introductionmentioning
confidence: 99%